Chemistry and evolution of the Piperaceae - Kato, Massuo J.; Furlan, Maysa [UNESP] (Int Union Pure Applied Chemistry, 2007)
The chemistry of members of the family Piperaceae is of great interest owing to the variety of biological properties displayed. A survey of structural diversity and bioactivity reveals that groups of species specialize in the production of amides, phenylpropanoids, lignans and neolignans, benzoic acids and chromenes, alkaloids, polyketides, and a plethora of compounds of mixed biosynthetic origin. Bioassays against Cladosporium cladosporioides and C. sphaerospermun have resulted in the characterization of various amides, prenylated phenolic compounds, and polyketides as potential classes of antifungal agents. Studies on the developmental process in seedlings of Piper solmsianum have shown that phenylpropanoid are produced instead of the tetrahydrofuran lignans found in adult plants. In suspension cultures of P. cernuum and P crassinervium, phenylethylamines and alkamides predominate, whereas in the adult plants prenylpropanoids and prenylated benzoic acids are the respective major compound classes. Knowledge of the chemistry, bioactivity, and ecology of Piperaceae species provides preliminary clues for an overall interpretation of the possible role and occurrence of major classes of compounds.
Keywords: Piperaceae; secondary metabolites; amides; chromenes; polyketides; lignans; mimetism